2014
DOI: 10.1002/bies.201400097
|View full text |Cite
|
Sign up to set email alerts
|

Now you see it: Genome methylation makes a comeback in Drosophila

Abstract: Drosophila melanogaster is often considered to lack genomic 5-methylcytosine (m(5) C), an opinion reinforced by two whole genome bisulfite-sequencing studies that failed to find m(5) C. New evidence, however, indicates that genomic methylation is indeed present in the fly, albeit in small quantities and in unusual patterns. At embryonic stage 5, m(5) C occurs in short strand-specific regions that cover ∼1% of the genome, at tissue levels suggesting a distribution restricted to a subset of nuclei. Its function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
2
20
0
5
Order By: Relevance
“…We could detect the distribution of methylated cytosine in pole cells of embryo ( Figure 5). Our observations corroborate with restricted distribution of methylated cytosine hypothesis of Boffelli et al 50 . Recently the importance of DNA methylation and Dmnt-2 mediated epigenetic regulation has been shown in WolbachiaDrosophila model system 51 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We could detect the distribution of methylated cytosine in pole cells of embryo ( Figure 5). Our observations corroborate with restricted distribution of methylated cytosine hypothesis of Boffelli et al 50 . Recently the importance of DNA methylation and Dmnt-2 mediated epigenetic regulation has been shown in WolbachiaDrosophila model system 51 .…”
Section: Discussionsupporting
confidence: 93%
“…melanogaster lacks both DNMT1 and DNMT3 genes and has a sparingly methylated genome. The role of DNMT-2 in methylation of D. melanogaster has been a matter of considerable debate 19,20,24,25,50 . It has been suggested that DNMT2 is indeed an RNA methyltransferase that uses a DNA methyltransferase type of mechanism 24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2004) and Boffelli et al. (2014) on Drosophila , Zemach et al. (2010) on flour beetles, and Walsh et al.…”
Section: Introductionmentioning
confidence: 99%